Effects of the first three doses of benralizumab on symptom control, lung function, blood eosinophils, oral corticosteroid intake, and nasal polyps in a patient with severe allergic asthma - Corrado Pelaia; Maria Teresa Busceti; Alessandro Vatrella; Marco Ciriolo; Eugenio Garofalo; Claudia Crimi; Rosa Terracciano; Nicola Lombardo; Girolamo Pelaia (SAGE Open Medical Case Reports, 2020)
Severe allergic eosinophilic asthma can be characterized by inadequate control, despite the regular use of high dosages of inhaled corticosteroids/long-acting β 2 -adrenergic agonists combinations, and the very frequent utilization of oral corticosteroids. Therefore, under these circumstances, an add-on biological treatment with monoclonal antibodies directed against suitable molecular targets, involved in the pathobiology of type-2 airway inflammation, is very useful. Within such a context, our case report refers to a 46-year-old woman with severe allergic eosinophilic asthma and relapsing nasal polyps, not eligible to add-on biological therapy with omalizumab because of her very high serum levels of immunoglobulins E (IgE). She is currently under treatment with the humanized monoclonal antibody benralizumab (30 mg subcutaneous injection, administered every 4 weeks for the first three doses, and every 8 weeks thereafter), an eosinophil-depleting anti-interleukin-5-receptor biologic. Our patient experienced relevant clinical and functional improvements already after the first dose, and subsequently striking changes were recorded after the second and third doses, including remarkable increases in asthma control test scores and forced expiratory volume in 1 s values, associated with a complete depletion of blood eosinophils and the interruption of oral corticosteroid intake, as well as with the concomitant disappearance of nasal polyps after the second dose. In conclusion, this case study suggests that benralizumab can exert a very rapid and effective therapeutic action in patients with severe eosinophilic asthma and nasal polyposis.